Swarm intelligence and bio-inspired computation : theory and applications - Yang, Xin-She; Cui, Zhihua; Xiap, Renbin; Gandomi, Amir Hossein; Karamanoglu, Mehmet (Elsevier insights., 2013)
Swarm Intelligence and bio-inspired computation have become increasing popular in the last two decades. Bio-inspired algorithms such as ant colony algorithms, bat algorithms, bee algorithms, firefly algorithms, cuckoo search and particle swarm optimization have been applied in almost every area of science and engineering with a dramatic increase of number of relevant publications. This book reviews the latest developments in swarm intelligence and bio-inspired computation from both the theory and application side, providing a complete resource that analyzes and discusses the latest and futu.